Die Privatisierung des mexikanischen Ejido - Hildebrandt, Susanne (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2002)
The article starts with an introduction into the structural changes on the world markets of agrarian goods occurred since the 1970s and its effects for the Mexican agrarian sector. As a consequence of the political shift towards an export oriented model in the countryside the Ejido and the peasants became dysfunctional. In 1992, the reform of article 27 of the Mexican Constitution brings the agrarian reform to an end. The case study of Ejido Sayula/Jalisco highlights the social and political implications of this historical reform.